New age constraints reveal moraine stabilization thousands of years after deposition during the last deglaciation of western New York, USA - K. K. Prince; J. P. Briner; C. K. Walcott; B. M. Chase; A. L. Kozlowski; T. M. Rittenour; E. P. Yang; E. P. Yang (Geochronology, 2024)
The timing of the last deglaciation of the Laurentide Ice Sheet in western New York is poorly constrained. The lack of direct chronology in the region has led to a hypothesis that the Laurentide Ice Sheet re-advanced to near its Last Glacial Maximum terminal position in western New York at ∼ 13 ka, which challenges long-standing datasets. To address this hypothesis, we obtained new chronology from the Kent (terminal) and Lake Escarpment (first major recessional) moraines using radiocarbon ages in sediment cores from moraine kettles supplemented with two optically stimulated luminescence ages from topset beds in an ice-contact delta. The two optically stimulated luminescence ages date the Kent (terminal) position to 19.8 ± 2.6 and 20.6 ± 2.9 ka. Within the sediment cores, there is sedimentological evidence of an unstable landscape during basin formation; radiocarbon ages from the lowest sediments in our cores are not in stratigraphic order and date from 19 350–19 600 to 14 050–14 850 cal BP. We interpret these ages as loosely minimum-limiting constraints on ice sheet retreat. Our oldest radiocarbon age of 19 350–19 600 cal BP – from a rip-up clast – suggests ice-free conditions at that time. Above the lowest sediments there is organic-rich silt and radiocarbon ages in stratigraphic order. We interpret the lowest ages in these organic-rich sediments as minimum-limiting constraints on kettle basin formation. The lowest radiocarbon ages from organic-rich sediments from sites on both Kent and Lake Escarpment moraines range from 15 000–15 400 to 13 600–14 000 cal BP. We interpret the 5 kyr lag between the optically stimulated luminescence ages and kettle basin formation as the result of persistent buried ice in ice-cored moraines until ∼ 15 to 14 ka. The cold conditions associated with Heinrich Stadial 1 may have enabled the survival of ice-cored moraines until after 15 ka, and, in turn, climate amelioration during the Bølling period (14.7–14.1 ka) may have initiated landscape stabilization. This model potentially reconciles the sedimentological and chronological evidence underpinning the re-advance hypothesis, which instead could be the result of moraine instability and sediment mobilization during the Bølling–Allerød periods (14.7–13 ka). Age control for future work should focus on features that are not dependent on local climate.